“Digital Image Processing Approach for Fruit and Flower Leaf Identification and Recognition” (International Journal of Engineering and Computer Science, 2013)
- Fruit and Flower trees are broadleaf and usually deciduous, meaning they lose their leaves annually in the fall. Knowing what types of fruit trees occur naturally will narrow the list of possibilities when trying to identify a tree. Observing the leaf of a tree or shrub is an excellent way to determine the species. Characteristics such as shape, size, texture and how the leaf is arranged can help identify the type of plant when fruit has not yet formed. Leaf features extraction on fruit leaf image is still be a problem on automatic plant leaf identification. This paper presents identification of local fruit trees through leaf structures using image processing techniques. In this study Chain code method is used which is used to obtain the shape of an object. Computer-Aided Plant Species Identification Technique (CAPSI) is used which is based on the image matching technique of leaf shape. The image pre-processing begins with converting the RGB image to the grey-scale image by applying thresholding technique before removing the noise. Sobel operator is applied to the binary image to recognize the edge of that image before thinning the edges. The feature extraction process is then conducted by using the chain code technique. The last stage is to recognize the leaves feature by using Linear Comparision technique.